Royal jelly acid: preparation, metabolism and therapeutic potential - Dandan Zhi; Xiying He; Yunfei Xue; Wenzheng Zhao; Xueyang Gong; Yulong Guo; Xinming Luo; Yakai Tian; Kun Dong (Frontiers in Pharmacology)
Royal jelly acid (10-HDA), an unsaturated fatty acid unique to royal jelly, exhibits a diverse range of biological activities, including hypoglycemic, anti-inflammatory, and anticancer properties. In recent years, the increasing demand for natural product supplements as health enhancers has led to a significant rise in the consumption of royal jelly products for daily wellness. Consequently, the market for royal jelly supplements has expanded considerably. Understanding the mechanisms underlying the biological activities of royal jelly acid is crucial for optimizing its therapeutic applications and guiding the development of innovative royal jelly-based products. This review consolidates current research on the preparation, metabolism and potential pharmacological roles of royal jelly acid in managing cancer, inflammatory disorders, and glucolipid metabolic diseases and explores the molecular mechanisms driving these effects. Future research should leverage advanced analytical techniques to uncover the intricate mechanisms of royal jelly acid’s actions, paving the way for its broader integration into healthcare and clinical settings.